An Overview of Theoretical Connections between the Rhetoric of Modernity and Postmodernity - Pandey, Hem Lal (Bon Voyage, 2024)
This paper explores the thematic convergences and departures within the rhetoric of modernity and postmodernity. In doing so, it explores some of their key themes such as language and meaning, reality and truth, autonomy and human progress, and reason concerning the works of Jurgen Habermas, John Locke, Jacques Derrida, Ferdinand de Saussure, Immanuel Kant and Jean Francois Lyotard. This paper employs a methodology of comparative textual analysis of the aforementioned authors’ selected texts and their themes in their historical/temporal positions within the discourse of the rhetoric of modernity and postmodernity. It fulfills two objectives: to explore what recurrent themes of modernity and postmodernity appear in the canonical theorists’ works, and to assess how they simultaneously overlap and differ from each other. Stepping on this comparative analysis, this paper brings together the thematic and theoretical connections between the rhetoric of modernity and postmodernity to conclude that the similarities and differences in the rhetoric of modernity and postmodernity among the selected theorists can be revisited through a thematic lens rather than the historical-temporal paradigms.